Evaluation of the antibiofilm activity of essential oils Cinnamomum cassia and Eugenia caryophyllus microencapsulated by spray drying (Revista Contexto & Saúde, 2026)
Biofilm-forming microorganisms are considered a challenge in terms of eradication in the areas of food, cosmetics, and health, as they are resistant to antibiotics and sanitizers available on the market. From this problematization, the essential oils (EOs) Cinnamomum cassia (CCEO) and Eugenia caryophyllus (ECEO) encapsulated in microparticles by the spray drying technique was used to obtain a stable dry emulsion and evaluate their antimicrobial action against biofilms of the microorganisms Staphylococcus aureus, Escherichia coli, and Candida albicans. The EOs were commercially obtained from different brands, being evaluated by the agar diffusion technique for preliminary evaluation of the antimicrobial action against the challenged microorganisms.  Microencapsulation was performed in spray drying, employing gum arabic and xanthan gum to obtain a dry emulsion with varying concentrations of the EOs. The microparticles were characterized for morphology, physicochemical parameters, and encapsulation efficiency (EE), and were also evaluated for anti-biofilm action. The results obtained showed relevant antimicrobial activity of the essential oils in non-encapsulated form and antibiofilm activity when they were microencapsulated, obtaining a significant logarithmic reduction concerning the initial load challenged, reducing between 3 to 4 logarithmic cycles. It was concluded that microparticles with encapsulated EOs showed promise in improving the stability of essential oils, with significant results when challenged against planktonic and sessile cells.
Keywords: Biofilme; Micropartículas; spray-drying; Óleos essenciais; anti-biofilme